Clinical Efficacy of Surgical Treatment in 40 Patients with Acute Hematogenous Osteomyelitis (Global Journal of Medical Research, 2020)
Objective: This study aimed to evaluate the diagnostic methods of acute hematogenous osteomyelitis and the clinical efficacy of fenestration decompression, focus debridement, and convective flushing. Methods: A retrospective analysis was performed on 40 patients with acute hematogenous osteomyelitis admitted to the Department of Orthopedics of our hospital from January 2011 to December 2018. There were 21 males and 19 females, aged 1#x2013;70 years, with an average age of 21.45 #xB1; 15.23 years, including 27 children and adolescents. The pathogenic sites were as follows: femur 20 cases, tibia 16 cases, humerus 2 cases, ulna 1 case, and radius 1 case. The systemic and local symptoms of patients before and after surgery were evaluated. The results of white blood cell count (WBC), NEUT%, hs-CRP, erythrocyte sedimentation rate (ESR), imaging examination, bacteriology, and pathological examination were analyzed. Fenestration decompression, focus debridement, and convective flushing were used at the site of lesion in the surgery.
Keywords: acute hematogenous osteomyelitis; surgical treatment; fenestration decompression; focus debridement